Barriers to Treatment among New York City Residents with Chronic Hepatitis C Virus Infection, 2014. (May 2016) - King, Andrea; Bornschlegel, Katherine; Johnson, Nirah; Rude, Eric; Laraque, Fabienne
Objective: New, highly effective hepatitis C virus (HCV) medications recently changed the landscape of HCV treatment. Access to treatment, however, is limited. The New York City Department of Health and Mental Hygiene conducted an enhanced surveillance project to better understand the reasons patients are not treated for HCV. Methods: In June 2014, we randomly selected 300 adults who were reported through routine surveillance as having a positive HCV ribonucleic acid test result and who had seen a medical provider since June 2012. We collected information on demographics, treatment, and barriers to treatment from these 300 patients and their providers by telephone, fax, mail, and medical record review. Results: Of 179 providers, 74 (41%) cited co-occurring conditions and 50 (28%) cited patients not keeping follow-up or referral appointments with specialists as common barriers to treatment. Forty providers (22%) reported that they do not prescribe HCV medications and instead refer patients to specialists for treatment. Of 89 patients citing barriers to treatment, 30 (34%) cited co-occurring conditions, 26 (29%) cited concerns about side effects, 21 (24%) indicated not feeling sick, 15 (17%) cited waiting for a better treatment regimen, and 12 (13%) cited medication costs or insurance issues. Only 11 providers and 10 patients denied any barriers to treatment. Conclusion: Increasing the number of New York City residents with HCV infection who are treated and cured will require programs to increase provider capacity, change provider behavior in treating patients with substance use and medical conditions, improve patient awareness of new medications, provide patient navigation and care coordination support through treatment, and initiate advocacy and policy work.